An Analysis of Types of English Slang Words and Strategies for Their Indonesian Translation in the Chappie Movie - Fransisca Ayu Renata; Lahay, Srisna J. (Universitas Cokroaminoto Palopo, 2024)
This study aims to identify the slang words and their translation strategies used in the Chappie movie released in 2015. This study uses descriptive qualitative methods. The data is analyzed using the theory of Partridge (2015) about slang words and Gottlieb (2005) about translation strategies. The data are collected from the script and subtitle of the movie Chappie. The study has found 126 slang words. There are 5 out of 11 types of slang found in this research. There are 106 data on society slang, 15 data on public house slang, 3 data on slang in public school and university, 1 data on slang in theatre, and 1 data on slang in medicine. There are 4 out of 10 types of translation strategies found in this research. There are 64 data of paraphrase, 33 data of transfer, 27 data of resignation, and 2 data of transcription. According to these findings, society slang is the most often used type of slang, and paraphrasing is the most commonly used translation strategy. Furthermore, this research can provide knowledge that is beneficial to readers and the next related research. More research is also needed to keep up with the progress of translation studies